Spheres of Desire: Tensions of Emotion and Consciousness in Clara Janés - Escobedo Bermúdez, Víctor (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
This paper investigates the relationship between consciousness and emotions through the representation of desire in the work Creciente fértil (1989) by Clara Janés. Contextualized within Cognitive Literary Theory, the study synthesizes several philosophical and neuroscientific considerations about desire with the purpose of proposing an interpretation of Clara Janés’ work based on the poetological hypothesis that the experience and satisfaction of desire fulfill a homeostatic function. From this derives an inquiry about the ways in which desire is intertwined with knowledge in literary language and about the structures of subjectivity with which poetic thought operates.
Keywords: Cognitive Literary Theory; Poetics; Desire; Emotions; Consciousness; Subjetivity; Clara Janés